Knowledge, attitude and practice regarding clinical and self breast examination among radiology professionals. (13th February 2019) - Rawashdeh, Mohammad; Zaitoun, Maha; McEntee, Mark F; Abdelrahman, Mostafa; Gharaibeh, Maha; Ghoul, Suha; Saade, Charbel
Aim: This study aims to assess the knowledge, attitudes and practices of radiology professionals in Jordan in regard to breast cancer (BC) screening.Methods: An IRB approved, online-based study was carried out in Jordan. The participants were radiologists (n = 8) and radiographers (n = 64).Results: The results showed that although 61.8% of participants were knowledgeable about BC prevention, only 65.7% (n = 48) of respondents performed breast self-examinations (BSE) on themselves, 28.7% (n = 21) underwent clinical breast examination (CBE) and 15.1% (n = 5) underwent either diagnostic or screening mammography.Conclusion: Radiology professionals are generally aware of the benefits of BC screening and its ability to facilitate early diagnosis of BC. Although some practitioners advise their relatives to perform BSEs and attend CBE, low percentages of respondents performed BSEs themselves or undergo CBE.